Variation of peripheral pulse transit time with internal vascular pressure changes induced by arm movement - Sun, Zhiwei; Jiang, Xinge; Wu, Hua; Liu, Feifei (Frontiers in Neuroscience, 2023)
Arm position influences arterial blood pressure and peripheral pulse transit time (PTT). This study aims to quantify the relationship between PTT changes with internal vascular pressure variations induced by the arm moving. Twenty-two healthy volunteers aged between 21 and 46 were recruited in this study. For each subject, with left arm at horizontal position as reference and the right arm moving from 90o to 45o, 0o, -45o, and -90o respectively, the 10 successive radial artery pulses segments obtained simultaneously from both arms. Pulse transit time (PTT) was calculated by the difference of the pulse foot between right arm and left arm within the same heartbeat. Change in blood pressure (BP) was calculated from the gravitational effect with the measured arm length. For 90o and 45o, changes in PTT were 17.1 and 11.4 ms respectively with the change rate of -1.19±0.60 ms (from 90o to 45o) and -0.79±0.39 ms (from 45o to 0o). While for -45o and -90o, changes of PTT were -3.0 and -3.3 ms respectively with the change rate of -0.21±0.23 ms (from 0o to -45o) and -0.06±0.27 ms (from -45o to -90o). Our results showed that the change in PTT with arm elevating is more obvious than that with arm lowering, indicating the different relationship between PTT changes due to the internal BP changes. This can help in understanding the inherent physiological/pathological mechanism of cardiovascular system.